Sosialisasi Pola Hidup Sehat Cegah Penyebaran COVID-19 Di Desa Labuhan Labo Kecamatan Padangsidimpuan Tenggara - Hidayah, Arinil; Daulay, Nanda Masraini (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Indonesia has declared Covid-19 a national disaster since March 14, 2020. Based on data from the Indonesian government, a total of 25,216 cases of patients were detected positive for Covid-19. In Indonesia, the first case of Covid-19 was announced on March 2, 2020. Most people infected with COVID-19 will experience fever and symptoms of respiratory problems such as coughing and shortness of breath. Older people, and those with other health problems such as cardiovascular disease, diabetes, chronic respiratory disease and cancer are more likely to develop serious problems. The best way to prevent and slow transmission is with good information about Covid-19, the disease it causes and how it spreads (World Health Organization, 2020). So based on the above problems, we intend to hold community service in the form of Socialization of a Healthy Lifestyle to Prevent the Spread of Covid-19 in the community as an effort to prevent the spread of Covid-19. The socialization activities carried out received a very positive response from the community, the community was happy to assist in posting flyers. The community was also very enthusiastic when given socialization with leaflet media and the curiosity of the community was also very high, seen from the many questions they submitted to the community service implementation team.